2021
DOI: 10.1021/acs.jpcc.1c02897
|View full text |Cite
|
Sign up to set email alerts
|

Boosted Structural Stability and Interfacial Charge Transfer in CmOnClk/[FA,MA]Pb1+yI3 Heterostructures

Abstract: We reported the first-principles computational study of the atomic-scale mechanism underlying the properties of C m O n Cl k /[FA,MA]­Pb1+y I3 heterostructures composed of graphene-related materials C m O n Cl k and formamidinium and methylammonium lead halide perovskites [FA,MA]­Pb1+y I3 (denoting [CH­(NH2)2, CH3NH3]­Pb1+y I3) with a Pb-rich surface that accounts for the proportion factor “y” of Pb. By investigating the structural and electronic properties, the charge carrier transfer, and the quantum transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In these two cases, the Pb atom is the preferred adsorption site. Charge redistribution mainly occurred near the bond region of the ligand [44] . Moreover, it was found that the binding energy of the CsPbI 3 NCs passivated by the HOPS ligand (1.88 eV) was much higher than that of the NCs passivated by the OA ligand (0.62 eV).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In these two cases, the Pb atom is the preferred adsorption site. Charge redistribution mainly occurred near the bond region of the ligand [44] . Moreover, it was found that the binding energy of the CsPbI 3 NCs passivated by the HOPS ligand (1.88 eV) was much higher than that of the NCs passivated by the OA ligand (0.62 eV).…”
Section: Resultsmentioning
confidence: 96%
“…Charge redistribution mainly occurred near the bond region of the ligand. [44] Moreover, it was found that the binding energy of the CsPbI 3 NCs passivated by the HOPS ligand (1.88 eV) was much higher than that of the NCs passivated by the OA ligand (0.62 eV). Such higher bonding strength between HOPS and CsPbI 3 NCs is less likely to cause ligand dissociation, thus avoiding the additional surface defects and structural deformation, which is conductive to maintaing the stability of CsPbI 3 NCs.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%